Modification of Visual Characters in Indonesia Animation Film - Ekawardhani, Yully Ambarsih; Santosa, Imam; Ahmad, Hafiz Azis; Irfansyah, Irfansyah (Harmonia: Journal of Arts Research and Education, 2020)
This study aims to determine the relationship between facial physiognomy, body shape, and visualization of animated film character designs. Characterization in an animated film is inseparable from the characters who are placed to fulfill the film’s role. In the creation of physiognomy and body shapes can be combined as an approach to design. The characters are modified through simplifications in the form of cartoons. This is done so that the visualization of the character gets closer to the role added, in addition to emphasizing the characteristics of one character to another. Even in animated films, characters become important elements to direct the understanding of stories. The approach used is interdisciplinary, given that in characters there is a merging of visual elements that need to be approached using different theories. The combination of theories used is personality theory through somatotype to find characters through body shapes, physiognomy from Ar-Razi and ming xiang to obtain character traits and the theory of simplifying shapes into cartoons. The result is a match between the characters played by the three reference elements. The interesting thing that was found was the application of different physiognomy between one character and another to reinforce the characteristics. So that in the film, these figures can represent roles, which are human presentations in real life.